Cyanation and cyanomethylation of trimethylammonium salts via electrochemical cleavage of C–N bonds. Issue 5 (25th January 2022) - Kong, Xianqiang; Wang, Yuchang; Chen, Yiyi; Chen, Xiaohui; Lin, Long; Cao, Zhong-Yan
Abstract : A practical and mild electrochemical protocol for cyanation and cyanomethylation of trimethylammonium salts has been developed. Abstract : We have developed a practical and mild electrochemical protocol for cyanation and cyanomethylation of trimethylammonium salts through a pathway involving C–N bond cleavage without the need for an external stoichiometric reducing agent or a sacrificial anode. The reaction employs tosyl cyanide (TsCN) or azido allyl alcohol as the cyanation or cyanomethylation reagent, respectively. It shows high functional group compatibility and can be applied for the cyanation of natural product derivatives. Preliminary mechanistic studies indicate the involvement of a radical addition pathway.